2005
DOI: 10.1021/tx050140s
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Human Cytochrome P450 Forms Involved in Metabolism of Tamoxifen to Its α-Hydroxy and α,4-Dihydroxy Derivatives

Abstract: Tamoxifen is a known hepatocarcinogen in rats and is associated with an increased incidence of endometrial cancer in patients. One mechanism for these actions is via bioactivation, where reactive metabolites are generated that are capable of binding to DNA or protein. Several metabolites of tamoxifen have been identified that appear to predispose to adduct formation. These include alpha-hydroxytamoxifen, alpha,4-dihydroxytamoxifen, and alpha-hydroxy-N-desmethyltamoxifen. Previous studies have shown that cytoch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 37 publications
2
21
0
Order By: Relevance
“…In conclusion, assessment of the kinetics of tamoxifen metabolism by expressed P450 enzymes suggest that tamoxifen ␣-hydroxylation is mediated primarily by CYP3A4, whereas tamoxifen N-demethylation is efficiently mediated by both CYP3A4 and CYP3A5. These findings corroborate previously published findings (Crewe et al, 1997;Desta et al, 2004;Notley et al, 2005). More importantly, our assessment using genotyped HLM strongly suggests that polymorphic expression of CYP3A5 significantly affects the in vitro clearance values for N-DMT formation but not ␣-OHT formation.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In conclusion, assessment of the kinetics of tamoxifen metabolism by expressed P450 enzymes suggest that tamoxifen ␣-hydroxylation is mediated primarily by CYP3A4, whereas tamoxifen N-demethylation is efficiently mediated by both CYP3A4 and CYP3A5. These findings corroborate previously published findings (Crewe et al, 1997;Desta et al, 2004;Notley et al, 2005). More importantly, our assessment using genotyped HLM strongly suggests that polymorphic expression of CYP3A5 significantly affects the in vitro clearance values for N-DMT formation but not ␣-OHT formation.…”
Section: Discussionsupporting
confidence: 92%
“…N-DMT is further hydroxylated by CYP2D6 to form endoxifen, which is a considerably more potent antiestrogen than TAM (Desta et al, 2004;Lim et al, 2006). Several earlier studies identified the role of CYP3A4 in the formation of N-DMT and ␣-OHT (Crewe et al, 1997;Desta et al, 2004;Notley et al, 2005). ␣-OHT is further activated by sulfotransferases to form an electrophilic carbocation that is capable of reacting with DNA.…”
Section: Introductionmentioning
confidence: 99%
“…The latter strongly inhibited CYP3A4 while also being metabolized by it. However, there are few reports about the inhibition of specific P450 isoenzymes by antitumor agents, eg, by thiotepa [42,43] , tamoxifen [44,45] and the less well-known sorafenib [46] . Our results showed that cytochrome P450 CYP3A4 did not metabolize C-1311 in cells, confirming our hypothesis that overexpression of this enzyme might modulate the cellular response of CHO cells following C-1311 treatment, even though CYP3A4 does not participate in metabolic transformations.…”
Section: Discussionmentioning
confidence: 99%
“…These results might have a strong impact on the drug-drug interaction in multidrug therapy because C-1311 was applied in phase II clinical trials with anthracyclines (Capizzi et al, 2008) and will be used with other therapeutic agents. Until now the inhibition of selected P450 isoenzymes was reported just for a few antitumor agents, e.g., thiotepa (Jacobson et al, 2002;Richter et al, 2005) and tamoxifen (Sridar et al, 2002;Notley et al, 2005). Other drugs delivered more examples, for instance, carbamazepine (Pearce et al, 2005(Pearce et al, , 2008 or 17␣-ethynylestradiol (Lin et al, 2002).…”
Section: Discussionmentioning
confidence: 99%